Electrical performance analysis and optimization of monofacial and bifacial crystalline silicon solar cells - Manikandan, A.V.M.; Prince, Shanthi (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
This paper presents the investigations and performance analysis of monofacial and bifacial crystalline silicon solar cells with PC1D simulation software. The fundamental limitation in the monofacial solar cell’s performance is its inability to absorb all the incoming solar radiation since the albedo effect (ground-reflected light that can be captured by the rear of the solar cell) is often neglected. So, the efficiency of the monofacial cell will be lower due to poor and incomplete optical absorption. Bifaciality helps to enhance the capturing of light in the solar cell, which means that the rear of the cell is exposed to solar radiation to produce electrical power. The primary focus of our work is to determine which solar cell offers better device performance and conversion efficiency by analyzing various parameters of the solar cell like surface texturing, emitter doping, bulk doping, minority carrier lifetime, bulk and surface recombination rates, front and rear reflectance, among other parameters. The other parameters are maintained at an optimal range to achieve the highest conversion efficiency. Our work has shown that the bifacial solar cell can be as efficient as 28.15%, which is much better than the 22.65% efficiency of the monofacial solar cell.
Optica Applicata, Vol. 53, 2023, nr 3, s. 327-351
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; silicon; monofacial solar cell; bifacial solar cell; PC1D; quantum efficiency; conversion efficiency; albedo; bifaciality factor; PERT